A simplified approach to develop fuzzy logic controller with disturbance estimator for control of a planar parallel (2PRP-PPR) motion platform. (May 2023) - Choudhury, Rutupurna; Londhe, Pandurang; Mohan, Santhakumar; Singh, Yogesh
This work presents, a robust position tracking control of a 3-degrees of freedom 2PRP-PPR (P: Active Prismatic joint, P: Passive prismatic joint, R; Revolute joint) parallel motion mechanism. For controlling the motion of the defined platform, a simple method to develop a fuzzy logic controller called as robust single input fuzzy logic control (RSIFLC) algorithm is presented and used for the complex workspace trajectory tracking control problem with the existence of outside disturbances, variable uncertainties, and inner noises. The suggested control method comprises two sections: The first section considers a feed-forward expression to increase control action and a disturbance estimator to account for anonymous factors like outer disturbances and un-modeled dynamics. The second section employs single input fuzzy logic control as a feedback component to improve the system's overall closed-loop stability. The experimental results demonstrate the superiority of the suggested control algorithm over traditional control schemes.